TESTING THE OMNIBUS LAW CONCEPT IN LEGAL THEORY: EVALUATING ITS EFFECTIVENESS AS A TOOL FOR SOCIAL ENGINEERING - Purwanda, Sunardi; Wiwin, Wiwin; Pransisto, Johamran; Musran, Andi (Faculty of Law, Universitas Lampung, 2024)
This research examines the enactment of Law Number 6 of 2023, which formalizes Government Regulation in Lieu of Law Number 2 of 2022 on Job Creation. The law reflects the Indonesian government's efforts to create and expand employment opportunities. However, it is crucial to investigate whether these efforts align with the broader interests of the community or merely serve the ruling elite's agendas. This study assesses whether the law, with its various mechanisms, effectively addresses social conditions in line with the government's objectives—such as reducing unemployment, accommodating new workers, and fostering the growth of cooperatives and MSMEs—or whether it diverges from these goals. A socio-legal approach is employed to analyze whether the government's interests genuinely reflect the community's needs.